Enzyme Mimetic Active Intermediates for Nitrate Reduction in Neutral Aqueous Media. Issue 24 (1st April 2020) - Li, Yamei; Go, Yoo Kyung; Ooka, Hideshi; He, Daoping; Jin, Fangming; Kim, Sun Hee; Nakamura, Ryuhei
Abstract: Nitrate is a pervasive aquatic contaminant of global environmental concern. In nature, the most effective nitrate reduction reaction (NRR) is catalyzed by nitrate reductase enzymes at neutral pH, using a highly‐conserved Mo center ligated mainly by oxo and thiolate groups. Mo‐based NRR catalysts mostly function in organic solvents with a low water stability. Recently, an oxo‐containing molybdenum sulfide nanoparticle that serves as an NRR catalyst at neutral pH was first reported. Herein, in a nanoparticle‐catalyzed NRR system a pentavalent Mo V (=O)S4 species, an enzyme mimetic, served as an active intermediate for the NRR. Potentiometric titration analysis revealed that a redox synergy among Mo V −S, S radicals, and Mo V (=O)S4 likely play a key role in stabilizing Mo V (=O)S4, showing the importance of secondary interactions in facilitating NRR. The first identification and characterization of an oxo‐ and thiolate‐ligated Mo intermediates pave the way to the molecular design of efficient enzyme mimetic NRR catalysts in aqueous solution. Abstract : In neutral : The nitrate reduction reaction (NRR) is essential for water remediation. In an artificial NRR catalyst, an enzyme mimetic intermediate has been identified for the first time in the activation of the NRR at neutral pH. The newly identified intermediate is stable in neutral water, and the secondary electronic interactions were found to play a key role.